Reproductive and Meat Performance of Pekin Ducks (P-11 and P-22) Under a Conservation Programme - Barbara Biesiada-Drzazga; Eugeniusz Wencek; Dorota Banaszewska (Animals)
The aim of this study was to evaluate selected reproductive traits and estimate selected meat traits of male and female ducks of strains P-11 and P-22 during the rearing period, in order to analyse the differences between the two duck populations in terms of these traits in three consecutive generations, i.e., in the years 2020–2022. The birds were kept at the Duck Breeding Centre in Lińsk, Kuyavian-Pomeranian Voivodeship. This study was conducted using all individually tagged individuals of both sexes of known origin and lineage. The birds were kept under standard conditions, and incubation and hatching were carried out in accordance with applicable technology. Reproductive traits were evaluated in three generations of ducks, and meat traits were evaluated during rearing. Ducks of strain P-11 were shown to have a higher laying rate than P-22 ducks, a higher egg fertilization rate, and higher hatching rates of healthy ducklings from set eggs and fertilized eggs, which confirms the differences between the two populations. Average egg fertilization rates during the three-year study period ranged from 92.38% to 94.71% in strain P-11 and from 91.37% to 92.80% in strain P-22. The rates of healthy ducklings hatched from set eggs ranged from 72.24% to 78.15% in strain P-11 and were 2.89% to 4.73% higher than for strain P-22. Egg weight at peak laying (above 80%) ranged from 91.9 to 92.3 g in strain P-22 and from 89.2 to 89 g in strain P-11, and the heritability coefficients for both strains were within the range for moderately heritable traits. Statistically significant differences were shown between the two populations for all meat traits evaluated during the rearing period, i.e., body weight at 3 and 7 weeks of age, keel length, and breast muscle thickness, in each of the three years of this study (three successive generations of birds). Male ducks had higher body weight, better musculature, and higher fat content than females. In addition, the males and females of strain P-22 had higher values for these traits than the birds of strain P-11. Minor changes were observed in successive generations in the values for these traits, as well as in the heritability coefficients estimated from variance for fathers (h2S), mothers (h2D), and fathers and mothers (h2SD). For most meat traits, the heritability coefficients estimated from the variance for fathers (h2S), mothers (h2D), and fathers and mothers (h2SD) took on values from low to high in both strains.